FRI0208 Metabolic Syndrome in Spondyloarthritis. Prevalence and Associated Factors. (9th June 2015) - Alonso Blanco-Morales, E.; Bravo-Ferrer, J.; Rey, R.; Bejerano, C.; Fernández, C.; Oreiro, N.; Silva, M.; Raga, A.; Graña, G.; De Aspe, B.; Acasuso, M.; De Toro, F.; et al.
Abstract : Background: It has been described a higher prevalence of metabolic syndrome (MetS) in patients with spondyloarthitis (SpA), particularly in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Objectives: To describe the prevalence of MetS in SpA patients identifying associated factors and to make a comparison between patients with AS and PsA. Methods: Observational and retrospective study of 410 SpA patients (188 AS according to modified New York criteria and 222 PsA according to CASPAR criteria) belonging to our follow-up cohort (2004-2014) of northwest of Spain. Demographic, clinical and laboratory data were collected corresponding to baseline visit. MetS was defined according to Adult Treatment Panel III (ATPIII) criteria. Qualitative variables were analyzed using Chi-square/Fisher test and for quantitative variables we used Student t/U Mann Whitney test. Statistical analysis was performed by SPSS 21.0 program. It was considered p<0.05 as significant. Results: Of the 410 patients, 68.3%, 280 were men (78% in AS and 60% in PsA, p<0.001), the mean age was 50 (±14) years without differences between AS and PsA. We could determine the prevalence of MetS in 287 patients; 37% (107) SpA patients fulfilled ATPIII criteria (47% in PsA versus 24% in AS, p<0.001). The percentages of each item considered in ATP III criteria are exposed in table 1 . We observed differences in high levels of blood glucose (32% in PsA and 16% in AS, p<0.001) and high blood pressure (72.2% in PsA and 61.7% in AS, p 0.035). MetS was related with male sex, high age and body surface mass (BMI), hyperuricemia and peripheral forms in the overall sample (p<0.05). In AS MetS was related with higher BASDAI and higher tragus-wall distance. Introducing significant and clinically relevant variables in the multivariate analysis, MetS was related with sex male (OR 4.9, CI 95% 1.85-12.79, p 0.001), higher BMI (OR 1.2 CI 95% 1.11-1.30 p<0.001) and PsA diagnosis (OR 2.7 CI 95% 1.12-6.51 p 0.027). Conclusions: We demonstrate an elevated prevalence of MetS in SpA patients; that is higher in PsA than in AS patients. These results highlight the importance of detection and early treatment of cardiovascular risk factors in SpA patients. Disclosure of Interest: None declared